2012
DOI: 10.1002/cbic.201200133
|View full text |Cite
|
Sign up to set email alerts
|

Giant Vesicles “Colonies”: A Model for Primitive Cell Communities

Abstract: Current research on the origin of life typically focuses on the self-organisation of molecular components in individual cell-like compartments, thereby bringing about the emergence of self-sustaining minimal cells. This is justified by the fact that single cells are the minimal forms of life. No attempts have been made to investigate the cooperative mechanisms that could derive from the assembly of individual compartments. Here we present a novel experimental approach based on vesicles "colonies" as a model of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
103
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 101 publications
(108 citation statements)
references
References 32 publications
(38 reference statements)
3
103
1
Order By: Relevance
“…Production of Permeable Giant Unilamellar Vesicles (GUVs)-FtsZ-containing GUVs were prepared according to a water-inoil emulsion method (30) to optimize the procedure described in Ref. 31.…”
Section: Methodsmentioning
confidence: 99%
“…Production of Permeable Giant Unilamellar Vesicles (GUVs)-FtsZ-containing GUVs were prepared according to a water-inoil emulsion method (30) to optimize the procedure described in Ref. 31.…”
Section: Methodsmentioning
confidence: 99%
“…Some of the most significant achievements concerning vesiclebased protocells include the incorporation of basic forms of replication 1 , communication 2 , transport 3 , biomolecule synthesis 4 , protein-protein interaction networks 5 and metabolism, amongst others [6][7][8][9][10][11] . There have also been significant advances in developing chemical and biological microreactors, either in vesicle or droplet form, that contain simple chemical reactions [12][13][14][15] .…”
mentioning
confidence: 99%
“…For example, it has been reported that lipid compartments can form clusters following simple adhesive forces [28,14]. Protein synthesis is still possible in such assemblies [27], and the idea of prototissue has been put forward, as supported by some pioneer work on membrane-to-membrane connective mojeties [49,42].…”
Section: Semi-synthetic Minimal Cells (Ssmcs)mentioning
confidence: 99%